2008
DOI: 10.1007/s00422-008-0236-y
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition, not excitation, is the key to multimodal sensory integration

Abstract: Multimodal neuronal maps, combining input from two or more sensory systems, play a key role in the processing of sensory and motor information. For such maps to be of any use, the input from all participating modalities must be calibrated so that a stimulus at a specific spatial location is represented at an unambiguous position in the multimodal map. Here we discuss two methods based on supervised spike-timing-dependent plasticity (STDP) to gauge input from different sensory modalities so as to ensure a prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…Theoretical studies have confirmed that excitatory and inhibitory teaching input can account for proper map alignment and thus development of multimodal space (Friedel and van Hemmen 2008;Davison and Frégnac 2006). It is, however, only by inhibitory teaching input that an already aligned map can be re-aligned later on (Friedel and van Hemmen 2008).…”
Section: Development Of Multisensory Spacementioning
confidence: 89%
See 2 more Smart Citations
“…Theoretical studies have confirmed that excitatory and inhibitory teaching input can account for proper map alignment and thus development of multimodal space (Friedel and van Hemmen 2008;Davison and Frégnac 2006). It is, however, only by inhibitory teaching input that an already aligned map can be re-aligned later on (Friedel and van Hemmen 2008).…”
Section: Development Of Multisensory Spacementioning
confidence: 89%
“…Although the precise nature of this teaching signal has not been clarified experimentally, selective neuronal disinhibition, or gating, seems to play a key role (Gutfreund et al 2002;Winkowski and Knudsen 2006). Theoretical studies have confirmed that excitatory and inhibitory teaching input can account for proper map alignment and thus development of multimodal space (Friedel and van Hemmen 2008;Davison and Frégnac 2006). It is, however, only by inhibitory teaching input that an already aligned map can be re-aligned later on (Friedel and van Hemmen 2008).…”
Section: Development Of Multisensory Spacementioning
confidence: 91%
See 1 more Smart Citation
“…In previous models of collicular map formation based on Hebbian plasticity (18,25), temporal correlations and response latencies were not considered, leaving out the potential significance of delayed inputs for instructive coding. By contrast, we interpret latency differences as a computational strategy of the brain, agreeing with the notion that latency coding is very prominent in the visual system and can be found as early as in the retina (26).…”
Section: Discussionmentioning
confidence: 99%
“…A special case of instructive coding, cross-modal spatial transformations, can be formed by spike-time-dependent plasticity (STDP) rules when driven by multimodal inputs (17,18). Although STDP by itself does not seem to be capable of supporting arbitrary instructive coding (19), we identify a possible scenario for the implementation of the perceptron rule, namely, in cells that display both SFA and STDP.…”
mentioning
confidence: 95%